A method for estimating radioactive cesium concentrations in cattle blood using urine samples. (4th August 2017) - Sato, Itaru; Yamagishi, Ryoma; Sasaki, Jun; Satoh, Hiroshi; Miura, Kiyoshi; Kikuchi, Kaoru; Otani, Kumiko; Okada, Keiji
Abstract: In the region contaminated by the Fukushima nuclear accident, radioactive contamination of live cattle should be checked before slaughter. In this study, we establish a precise method for estimating radioactive cesium concentrations in cattle blood using urine samples. Blood and urine samples were collected from a total of 71 cattle on two farms in the 'difficult‐to‐return zone'. Urine 137 Cs, specific gravity, electrical conductivity, pH, sodium, potassium, calcium, and creatinine were measured and various estimation methods for blood 137 Cs were tested. The average error rate of the estimation was 54.2% without correction. Correcting for urine creatinine, specific gravity, electrical conductivity, or potassium improved the precision of the estimation. Correcting for specific gravity using the following formula gave the most precise estimate (average error rate = 16.9%): [blood 137 Cs] = [urinary 137 Cs]/([specific gravity] − 1)/329. Urine samples are faster to measure than blood samples because urine can be obtained in larger quantities and has a higher 137 Cs concentration than blood. These advantages of urine and the estimation precision demonstrated in our study, indicate that estimation of blood 137 Cs using urine samples is a practical means of monitoring radioactive contamination in live cattle.